2007
DOI: 10.2151/jmsj.85a.271
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Atmospheric Temperature in the Upper Troposphere and Cumulus Convection over the Eastern Part of the Tibetan Plateau in the Pre-Monsoon Season of 2004

Abstract: In the spring of 2004, we implemented intensive field observations in the eastern part of the Tibetan Plateau. In this study, we use the field observation data, as well as satellite observation data and reanalysis data, to examine increases in diurnal potential temperature and variations in atmospheric conditions over the eastern part of the Tibetan Plateau. The results of intensive radiosonde observations reveal a significant temperature increase attaining to the tropopause in April. The depth of the mixing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…Thus, the potential temperature increased in the free atmosphere above around 4 km under the condition of cumulus convection (figure not shown). Such atmospheric heating in the upper troposphere was also observed in spring at the Tibetan Plateau (Taniguchi and Koike 2007). In contrast to this case, the vertical winds were weak and a cumulus cloud was not observed on DOY 158 in 2005.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Thus, the potential temperature increased in the free atmosphere above around 4 km under the condition of cumulus convection (figure not shown). Such atmospheric heating in the upper troposphere was also observed in spring at the Tibetan Plateau (Taniguchi and Koike 2007). In contrast to this case, the vertical winds were weak and a cumulus cloud was not observed on DOY 158 in 2005.…”
Section: Resultsmentioning
confidence: 49%
“…A strong vertical wind, which can reach the free atmosphere, develops in the ABL over the plateau in early summer . Over the Tibetan Plateau, dry convection in the ABL and cumulus convection have been shown to play significant roles in heating the upper troposphere in spring (Taniguchi and Koike 2007). Thus, the developments of the ABL and clouds are critical factors in atmospheric dynamics and water cycles.…”
mentioning
confidence: 99%
“…The first intensive in situ observations during early spring upon the Plateau were performed in April 2004 under the framework of the Coordinated Enhanced Observing Period (CEOP) (Koike 2004). Based on in situ and satellite observations, and numerical simulations, Taniguchi and Koike (2007) reported the importance of cumulus activity in terms of increases in atmospheric temperature in the upper troposphere, even in April. In the boreal winter, the change of the heat source across the Plateau may breed out abnormal zonal winds over the equatorial Pacific Ocean, which in turn may result in an abnormal sea surface temperature that would eventually a¤ect ENSO events (Chen et al 2001).…”
Section: Background and Motivationmentioning
confidence: 99%
“…From the point of view of cloud convections, Fujinami and Yasunari (2001) found an active convective season over the plateau from March to April by satellite images, and Oku and Ishikawa (2004) also indicated a robust decrease of the cloud free ratio in the same season. According to an intensive sonde observation in April by Taniguchi and Koike (2007), mid-tropospheric warming was associated with cumulous convections, and a numerical simulation demonstrated the necessity of condensation processes to initiate the convection. Those studies indicated that the heating process of the plateau surface has already started in early spring, when the retreat of snow covers and development of topsoil melting layer are activated under the rich subtropical solar radiation.…”
Section: Introductionmentioning
confidence: 99%